Evaluation of the impact of oximeter averaging times on automated FiO2 control in routine NICU care: a randomized cross-over study - J. Janota; J. Dornakova; V. Karadyova; R. Brabec; V. Rafl-Huttova; T. Bachman; M. Rozanek; J. Rafl (Frontiers Media S.A., 2023)
ObjectiveChanges in oximeter averaging times have been noted to affect alarm settings. Automated algorithms (A-FiO2) assess FiO2 faster than oximeter averaging, potentially impacting their effectiveness.MethodsIn a single NICU routinely using 15 fabian-PRICO A-FiO2 systems, neonates were randomly exposed to SpO2 averaging time settings switched every 12 h among short (2-4 s), medium (10 s), and long (16 s) oximeter averaging times for the entire duration of their A-FiO2 exposure. Primary endpoints were the percent time in the set SpO2 target range (dependent on PMA), SpO2 < 80%, and SpO2 > 98%, excluding FiO2 = 0.21.ResultsTen VLBW neonates were enrolled over 11 months. At entry, they were 17 days old (IQR: 14-19), with an adjusted gestational age of 29 weeks (IQR: 27-30). The study included data from 272 days of A-FiO2 control (34% short, 32% medium, and 34% long). Respiratory support was predominantly non-invasive (53% NCPAP, 40% HFNC, and 6% NIPPV). The aggregate SpO2 exposure levels were 67% (IQR: 55-82) in the target range, 5.4% (IQR: 2.0-10) with SpO2 < 80%, and 1.2% (IQR: 0.4-3.1) with SpO2 > 98%. There were no differences in the target range time between the SpO2 averaging time settings. There were differences at the SpO2 extremes (p ≤ 0.001). The medium and long averaging were both lower than the short, with the difference larger than predicted. Multivariate analysis revealed that these findings were independent of subject, ventilation mode, target range, and overall stability.ConclusionsThis A-FiO2 algorithm is effective regardless of the SpO2 averaging time setting. There is an advantage to the longer settings, which suggest an interaction with the controller.